2021
DOI: 10.1186/s12891-021-04721-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Baker cyst volume, with emphasis on cartilage lesion degree and effusion in the young and middle-aged population

Abstract: Background The principal aim of this study was to investigate the presence of factors affecting Baker’s cyst volume in young and middle-aged populations. Methods Open cyst excision with valve and capsule repair, as well as knee arthroscopy, were used to treat eighty-five patients. The cases were categorized in terms of age, effusion, chondral lesion degree, meniscal tear degree, and Lindgren scores. An ultrasonography (USG) device was used to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Also, another study showed that there is a significant correlation between the size of the BC and the stage of OA according to the Kellgren-Lawrence classification. This study found that BC is more common in patients with advanced stages of OA and that cyst size is directly proportional to the severity of OA [25].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also, another study showed that there is a significant correlation between the size of the BC and the stage of OA according to the Kellgren-Lawrence classification. This study found that BC is more common in patients with advanced stages of OA and that cyst size is directly proportional to the severity of OA [25].…”
Section: Discussionmentioning
confidence: 53%
“…Researching the international databases regarding the change in size of the BC depending on various factors, we conclude that there are not much data regarding this aspect. It seems that there is evidence that an increase in chondral lesion severity increases the amount of effusion and cyst volume, the degree of chondral lesion was moderately and positively correlated with cyst volume in the total population, and the degree of the chondral lesion was moderately and positively correlated with the degree of effusion [25]. At the same time, cartilage degeneration, medial plicae, and an increase in intra-articular effusion may increase the BC volume [34].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical conditions, such as inflammatory or degenerative arthropathy, which can cause increase of intra-articular pressure due to increase of joint effusion, the effusion may enter into the cyst. Furthermore, development of Baker’s cyst was associated with ACL tear and meniscal tear [ 15 16 17 ]. Therefore, it was thought that there may be factors contributing to the cyst rupture, just as there were many factors affecting the cyst development.…”
Section: Discussionmentioning
confidence: 99%
“…However, advanced degenerative changes within the knee is a relative contraindication to arthroscopic management. 7 Given the patient's clinical history, examination, and imaging findings, the patient was indicated for right knee arthroscopic partial medial meniscectomy and a popliteal cyst decompression.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…However, advanced degenerative changes within the knee is a relative contraindication to arthroscopic management. 7…”
Section: Video Transcriptmentioning
confidence: 99%